Understanding the Roles and Responsibilities of Healthcare Assistants in Health Care Security, Dentists, Pharmacy Technicians, and Medical Secretaries in Care Coordination and Improving Patient Experience in Saudi Arabia: A Qualitative Study - Mamdouh Jassim Oqlaa Alkhaldi; Abdullah Faleh Fehaid Alsubaie; Ahmed Hawash Alshammari; Yosef Hyyan Alrwily; Qasem Mohammed Hamoud Aldhafeeri; Fahhad Jarad Silfiq Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective: This qualitative study aimed to explore and understand the crucial roles played by healthcare assistants in maintaining health care security, as well as the contributions of dentists, pharmacy technicians, and medical secretaries in care coordination and enhancing patient experience within the healthcare system of Saudi Arabia. Methods: Semi-structured interviews were conducted with 40 healthcare professionals, including 10 healthcare assistants, 10 dentists, 10 pharmacy technicians, and 10 medical secretaries, who were purposively sampled from various healthcare facilities across Saudi Arabia. Thematic analysis was employed to identify key themes and patterns in the data. Results: The analysis revealed several key themes: 1) Healthcare assistants play a vital role in maintaining health care security by ensuring patient safety, infection control, and facility security; 2) Dentists contribute to care coordination by collaborating with other healthcare professionals and providing comprehensive oral health care; 3) Pharmacy technicians enhance care coordination through medication management and patient education; 4) Medical secretaries facilitate care coordination by managing appointments, medical records, and communication between healthcare providers and patients; 5) All four roles contribute to improving patient experience by providing patient-centered care, effective communication, and emotional support. Conclusion: This study highlights the essential roles and responsibilities of healthcare assistants, dentists, pharmacy technicians, and medical secretaries in care coordination and improving patient experience within the Saudi Arabian healthcare system. The findings emphasize the importance of recognizing and supporting these roles to enhance the quality and efficiency of healthcare delivery.